2007
DOI: 10.1007/s10461-007-9300-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Respondent Driven Sampling for Recruiting Males Who have Sex with Males in Dhaka, Bangladesh

Abstract: This paper evaluates the effectiveness of respondent driven sampling (RDS) to sample males who have sex with males (MSM) in Dhaka, Bangladesh. A major objective for conducting this survey was to determine whether RDS can be a viable sampling method for future routine serologic and behavioral surveillance of MSM as well as other socially networked, hard to reach populations in Bangladesh. We assessed the feasibility of RDS (survey duration; MSM social network properties; number and types of initial recruits) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 16 publications
2
63
2
1
Order By: Relevance
“…Specifically, initial participants are generally a convenience sample and are almost certainly not chosen in the judicious, independent manner of our simulations (40). There is also evidence of nonrandom recruitment of peers and of differential participation and recruitment rates (40)(41)(42)(43)(44). In a study of MSM in Brazil (45), for example, participants were more likely to recruit those who they thought engaged in riskier behavior and who would therefore most benefit from HIV testing; this same study found that some individuals refused to participate for fear of disclosing their sexual orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, initial participants are generally a convenience sample and are almost certainly not chosen in the judicious, independent manner of our simulations (40). There is also evidence of nonrandom recruitment of peers and of differential participation and recruitment rates (40)(41)(42)(43)(44). In a study of MSM in Brazil (45), for example, participants were more likely to recruit those who they thought engaged in riskier behavior and who would therefore most benefit from HIV testing; this same study found that some individuals refused to participate for fear of disclosing their sexual orientation.…”
Section: Resultsmentioning
confidence: 99%
“…Although not explicitly called an incentive, clinical examinations and testing and test results are seen by some target populations as an inducement to participate in the survey. MSM in Bangladesh (2006) and SWs in Northeastern India (2005), for example, reported participating in the study because of the clinical examination and/or test results they were offered (Johnston et al 2007b). SWs in São Paulo, Brazil (2005) reported being more interested in the rapid HIV test and results than in another type of incentive.…”
Section: Designating Appropriate Incentivesmentioning
confidence: 99%
“…In Bangladesh, MSM were found to have diverse network patterns by self-identified type of MSM (e.g., bisexual, khoti, Panthi, etc.) (Johnston et al 2007b). Other studies have found that some populations do not form diverse social network connections for certain characteristics.…”
Section: Social Networkmentioning
confidence: 99%
“…A new method called respondent-driven sampling (RDS) lends statistical rigor to conventional snowball sampling through longer recruitment chains, recruitment limits, and the collection of data used to statistically adjust for the biases inherent in how persons of similar characteristics are networked and likely to recruit each other (Heckathorn 1997;Ramirez-Valles et al 2005). RDS is still an experimental methodology being used for surveillance of populations most-at-risk for HIV/AIDS in the United States and in more than 83 countries worldwide (Johnston et al 2007). Although statistical questions about RDS remain, there is a growing body of experience using the method.…”
Section: Introductionmentioning
confidence: 99%